Towards luminescent ethnography of creative work: Purity, dirt and social inequality in Russian art institutions. (February 2023) - Kuleva, Margarita I
This article investigates the idiosyncrasies of creative work in Russian art institutions through a study of their materialities. As identified in previous research, social inequalities are a significant feature of creative work. I argue, however, that in order to reveal inequalities that are constructed performatively, that is, in the 'here' and 'now', we need to further develop the existing arsenal of methods that is employed in critical creative work studies. In the Russian case, art institutions display a wealth of techniques for constructing and maintaining hierarchies, which of necessity must frequently be re-established due to conditions in the local context. In particular, the following explores two perennial paradigms of cultural production: 'high culture' and 'creativity'. As these paradigms coexist in the economy of the Russian art world, they compete for resources, including funding, public attention and legitimation. In the struggle, a binary of purity/dirt develops the social space of institutions, organisational identities and hierarchies inside and between organisations. This paper primarily focuses on an ethnographic study of cultural producers from the visual arts sector in Russia's two largest cities: Moscow and St. Petersburg.